Media Sosial dan Internalisasi Nilai Pancasila dalam Pembentukan Karakter Mahasiswa yang Berjiwa Nasionalis - Anna Christina Ikasari; Asti Sri Mulyanti; Yoana Nurul Asri (Pusat Riset dan Inovasi Nasional, 2025)
Social media is not merely a space for entertainment. It has become part of students’ daily lives. Through these platforms, various values, ideologies, and discourses on nationalism circulate constantly. This study aims to examine how far social media contributes to the internalization of Pancasila values and the formation of nationalist character among university students. This research used a descriptive quantitative survey method. A total of 50 students from various majors served as respondents. They completed a questionnaire distributed via Google Form. The results show that 90% of students actively use social media. About 72% claim to have a nationalist attitude, and 76% show social concern. However, only 42% apply Pancasila values in their daily lives. Participation in community activities and national discussions is relatively low. Furthermore, 64% of respondents expressed disappointment toward state institutions. This disappointment is influenced by exposure to issues such as corruption allegations and controversial national policies. From these findings, it is clear that social media can serve as an educational platform, but it may also become an entry point for a crisis of trust. The internalization of Pancasila values has not yet been fully effective. There is a gap between understanding and actual behavior.